Electoral Integrity and Quality of Democracy in Sub-Saharan Africa: The Case of Mozambique - Jochua Abrao Baloi (Polit Journal Scientific Journal of Politics, 2023)
This article comes about with the objective of analyzing the electoral integrity and the quality of democracy in sub-Saharan Africa, considering the case of Mozambique. The main argument that guides this article is that, in the case of Mozambique, electoral cycles are characterized by problems of electoral integrity, more due to the political centralism adopted by the ruling party, Frelimo. To support this argument, can be advanced a premise according to which the political centralism adopted by Frelimo was inherited from the colony, from the militarism of the struggles for independence and perfected in the socialist period. From a qualitative and multidisciplinary approach centered on African history and political science, this article concludes that, although Mozambique is formally a democratic country, its political practices denote that it is a country with problems of electoral integrity.